RESPON KOMUNITAS BENTHIK INSEKTA EMPAT BULAN PASCA-KEBAKARAN HUTAN 2002 DI HULU KALI BOYONG GUNUNG MERAPI - Tjut Sugandawaty Djohan (Universitas Gadjah Mada, 2015)
The purpose of this research is to study the response of benthic insect community in the headwater of BoyongRiver, Mount Merapi, four months post-forest fire in 2002. Energy at the headwater ecosystem was based on thedetritus food-chain. The presence of benthic community indicated forest health. The forest fire caused energy whichentered into the river changed from allochtonous coarse particulat organic matter (CPOM) to fine particulatorganic matter (FPOM). This change would be responded by the functional group of benthic community. Datawere collected with Surber Sampler. The result showed that there were 12 genus constituent of benthic insectsconsisted of functional groups of collector gather, collector filter, predator, dan scrapper. The dominant functionalgroups were collector gather and collector filters, 2256 individual/m3 or 86.02% and the dominant genus of Baetisand Leutcra. Otherwise, scrapper was founded 111 individual/m3 or 4% and predator 256 individual/m3 or 10%.This condition showed that four months post-forest fire indicated dominant allochtonous in Boyong River wasCPOM and FPOM with size of 1 mm. The quality of nutrients in the water was low, otherwise, the sedimentnutrients was high. The dominance of functional group of collectors indicated that ecosystem of headwater forestin Boyong River had not been fully recovered.